Quantity Evaluation of Laactic Acid Bacteria Using the Fncc 0027 and C410li Gene on Different Storage of Acid Bamboo - Putri Widelia Welkriana; Halimatussa'diah Halimatussa'diah (Jurnal Analis Medika Biosains (JAMBS), 2023)
The fiber content in bamboo shoots is higher than other tropical vegetables. The water content in saw bamboo shoots is quite high, causing the bamboo shoots to have a shelf life of only 2 days. The fermentation process is characterized by the conversion of carbohydrates into lactic acid by bacteria. This study aimed to calculate LAB with FNCC 0027 and C410LI genes in tamarind shoots with different storage periods. The method used in this study is a descriptive method to describe the total plate number of microbes, LAB examination and molecular identification of bacteria found in tamarind shoots with different storage times. The results showed that all samples showed the presence of microbial TPC, examination. As for molecular identification, it was found that samples 1, 2, and 3 were identified as LAB with the C4101LI gene, while the FNCC0027 gene was not detected. Concluded that the total plate number values with different storage times of tamarind shoots, namely 0, 24, and 48 hours were 2.5x105 CFU/g, 5.4x105 CFU/g, and 7.3x105 CFU/g. In samples 1, 2, and 3, there were lactic acid bacteria of the type Bacillus plantarum C401L1.